Aluminium Anodizing Sebagai Material Alternatif Velg Kendaraan - Mulyaningsih, Nani -; Pramono, Catur; Dwi Ratnasari, Emma; Faishal, M. Noor; Putra, Exnacius (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Aluminum is a type of metal lightweight and easy to shape so it is widely used for several applications including vehicle wheels. The surface of vehicle wheels needs a certain roughness/smoothness to be more aesthetically appealing and production defects during the manufacturing process can be reduced. Anodizing on aluminum has been studied before, but so far there are still not many studies that specifically analyze the results of anodizing on surface smoothness. The purpose of this study is to analyze the roughness of aluminum anodization results when varying the immersion time. Results of this study are compared to the standard roughness of vehicle wheels. The method used is the anodizing process with variable anodizing times of 40, 45, 50, 55, 60, 65 minutes. Then surface roughness testing was carried out using a roughness tester. The results showed that anodizing time plays a role in determining the surface roughness / smoothness of the material. The longer the anodizing time the rougher the resulting surface. The best roughness value occurs in the 40-minute time variation with a roughness value of 0.7683 µm and can meet the DIN 3760 quality standard. With this information, an alternative material to replace vehicle wheels The purpose of this study is to analyze the roughness of aluminum anodizing results by varying the soaking time. The results of this study were compared with the standard roughness of car wheels.